Growth, yield, quality and economics of Annona (Annona squamosa L.) based hortipasture system as influenced by Stylosanthes species and fertility levels under rainfed condition - Ram, S.N.; Kumar, Sunil (Indian Journal of Agroforestry, 2020)
A field experiment was conducted during 2002-2003 to 2004-2005 on six years old Annona orchard planted at 6 m apart at Central Research Farm of Indian Grassland and Fodder Research Institute, Jhansi to study the effect of Stylosanthes species (Stylosanthes hamata and S. scabra), phosphorus and potash levels (P2O5 and K2O at 0-0, 20-15, 40-30 and 60-45 kg/ha) on productivity and economics of Â buffel grass + Annona based hortipasture system. Buffel grass intercropped with S. hamata in association with Annona trees recorded significantly higher dry forage (5.95 t/ha) and crude protein yield (503.4 kg/ha) when compared to S. scabra. The maximum net return (Rs 13710/ha) and benefit: cost ratio (1.52) was also obtained with intercropping of S. hamata and buffel grass under Annona trees. Dry forage yield and fruit quality of Annona increased significantly with increase in phosphorus and potash level from control to 40 kg P2O5 and 30 kg K2O/ha which was at par with that of 60 kg P2O5 + 45 kg K2O/ha. However, crude protein yield (545.3 kg/ha) and fruit yield (7.14 kg/tree) increased significantly upto 60 kg P2O5 + 45 kg K2O/ha. Application of phosphorus and potash also had a positive effect on maintenance of legumes population. Persistence of legumes were 91.8 and 84.3 per cent in the treatment where phosphorus and potash was applied @ 60 + 45 kg/ha as compared to control treatment (78.3 and 67.2 per cent) during the second and third years, respectively. The highest net return (Rs. 15591/ha) and benefit: cost ratio (1.61) was also accrued with application of 60 kg P2O5/ha + 45 kg K2O/ha from Annona based hortipasture system.